Keabsahan Perjanjian Kerja Waktu Tertentu Yang Dibuat Secara LisanMenurut Undang-Undang Ketenagakerjaan - Andre Setiawan; Afrina Mayang W; Ahmad Zulfi K; Pramudita D; Yohanes P. Simanjuntak (Wijayakusuma Law Review, 2023)
Workforce is an important part of a company, without which the company cannot function. Based on regulations, theworkforce is governed by an employment agreement system which is divided into fixed-term employmentagreements (PKWT) and indefinite-term employment agreements (PKWTT). Further regulations regarding fixedterm employment agreements are stipulated in Article 56 and 57 of Law No. 13 of 2003 on employment. Based onthese regulations, it is known that a fixed-term employment agreement (PKWT) must be made in writing and mustuse the Indonesian language and Latin letters. However, in practice, there are still business operators who employworkers without complying with the existing regulations. A dispute arose between PT. SRIKANDI INTI LESTARI asthe employer and the workers named Sentosa, Sukardi Oloan, Sholikin, Tumpal Marsaor Pangihutan, Baos AlbertSilalahi, Akhiar, Nurwedi, and Arse, who are employees working at PT. SRIKANDI INTI LESTARI. It was found thatthe workers worked under a contract status as fixed-term employees (PKWT) continuously and sustainably for morethan 3 (three) years without any break. Among the employment contracts, some of them were not made in writing,but were only agreed upon orally.